Analisis Mengatasi Kejenuhan Belajar Siswa Pada Pembelajaran Ilmu Pengetahuan Sosial Materi Globalisasi Di Kelas VI SDS IT Al-Fauzi Medan Amplas - Annisa Arnun; Nuraida; Savira Maharani; Mhd Arif Setiawan (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2021)
This study intends to explain learning boredom and ways to overcome it to students in Grade VI at SDS IT Al-Fauzi Medan Amplas. The type of study used is a qualitative descriptive study where all data has been collected by selecting data to obtain quality data, the data collection techniques used are observation and interviews. The results are (1) Efforts to overcome student learning saturation in class VI SDS IT Al-Fauzi Medan Amplas are to make various ways, such as varied learning methods, make the same approach as students and make evaluations at the end of learning activities where it is feedback on the KBM process , which is used as a reference to improve and increase interest in learning (2) The link in how to overcome boredom can be seen from students when studying, because the methods used when teaching are varied and are not fixed on lectures, especially on globalization material which is considered quite important in social studies learning.